La metodología juego trabajo en el desarrollo de habilidades cognitivas de los niños y niñas de 3 a 4 años de inicial II en la unidad educativa “Ángel Polibio Chaves” provincia de Bolívar cantón Guaranda, periodo 2024 - Moreta Quintuña, Gissel Vanesa (2025)
This research analyzes the impact of the play-work methodology on the development of cognitive skills in boys and girls aged 3 to 4 years in the “Ángel Polibio Chaves” Educational Unit during the period 2024. The main challenge identified is the limited application of strategies. playful activities in the classroom, which has a negative impact on the development of skills such as memory, attention and problem solving. This highlights the importance of adopting innovative pedagogical approaches that integrate meaningful learning with playful activities, creating a more attractive and effective educational environment. The focus of the study is to analyze how this methodology influences children's cognitive development, with emphasis on identifying appropriate recreational activities, theoretically substantiating its application and designing a pedagogical guide for teachers. Based on the theories of Piaget, Vygotsky and Gardner, it is emphasized that planned play not only promotes cognitive development, but also promotes social and emotional skills crucial for the comprehensive growth of children. It is expected to demonstrate that the play-work methodology is an effective pedagogical tool and adaptable to other educational environments, especially those with limited resources. The findings of this study will not only benefit the “Ángel Polibio Chaves” Educational Unit, but will also serve as a basis to strengthen inclusive and innovative educational practices focused on comprehensive development in early education